Cascade-type energy band design of a black phosphorus photodetector with high performance. Issue 8 (19th December 2018) - You, Congya; Zhang, Guoqing; Deng, Wenjie; Zhao, Chen; An, Boxing; Liu, Beiyun; Wang, Bo; Yan, Hui; Liu, Danmin; Zhang, Yongzhe
Abstract : A high performance hybrid black phosphorus/PbS QD photodetector with an additional junction through ligand-based energy band engineering. Abstract : The hybrid-induced photogating effect using colloidal quantum dots is usually utilized to optimize the performance of 2D-based photodetectors, where the 2D material is usually black phosphorus, transition metal dichalcogenides or graphene. However, the method of integrating a single-layer light absorber material with 2D materials for increasing the photoresponse has suffered from limited depletion width so it can hardly achieve our desired application. Here, we proposed a hybrid BP/lead sulfide quantum dot photodetector with a cascade-type energy band structure, which can greatly improve the performance of this photodetector compared with a single-layer absorber. This device can display a high responsivity of 1.1 × 10 7 A W −1, a high detectivity of 1.75 × 10 15 Jones, and a low noise equivalent power of 4.3 × 10 −7 pW Hz −1/2 simultaneously. These results indicate that a cascade-type energy band structure is not only able to effectively enhance the performance of the hybrid BP/lead sulfide quantum dot photodetector but also has great potential for wide application in other 2D material-based optoelectronic devices.